Interaction of Human Respiratory Syncytial Virus (HRSV) Matrix Protein with Resveratrol Shows Antiviral Effect - Rodrigues, Thaina [UNESP]; Busso, Jefferson de Souza [UNESP]; Dias, Raphael Vinicius Rodrigues [UNESP]; Ottenio Lourenço, Isabella [UNESP]; de Sa, Jessica Maróstica [UNESP]; Carvalho, Sidney Jurado de [UNESP]; Caruso, Icaro Putinhon [UNESP]; Souza, Fatima Pereira de [UNESP]; Fossey, Marcelo Andres [UNESP] (MDPI, 2024)
The respiratory syncytial virus (RSV) matrix protein plays key roles in the virus life cycle and is essential for budding, as it stimulates the optimal membrane curvature necessary for the emergence of viral particles. Resveratrol, a polyphenol (3,4′,5-trihydroxy-trans-stilbene) produced by plants, exhibits pharmacological effects, including anti-inflammatory and antiviral activities. In this study, resveratrol was tested in HEp-2 (Epidermoid carcinoma of the larynx cell) cells for its post-infection effects, and recombinant M protein was produced to characterize the biophysical mechanisms underlying this interaction. The CC50 (Cytotoxic concentration 50%) value for resveratrol was determined to be 297 μM over 48 h, and the results from the HEp-2 cell cultures demonstrated a viral inhibition of 42.7% in the presence of resveratrol, with an EC50 (Half maximal effective concentration) of 44.26 μM. This mechanism may occur through interaction with the M protein responsible for the budding of mature viral particles. Biophysical assays enabled us to characterize the interaction of the M/resveratrol complex as an entropically driven bond, guided by hydrophobic interactions at the dimerization interface of the M protein, which is essential for the stabilization and formation of the oligomers necessary for viral budding. These findings suggest that one of the targets for resveratrol binding is the M protein, indicating a potential site for blocking the progression of the infection.
Keywords: and resveratrol; M protein; respiratory syncytial virus